The current role of ultrasound in the assessment of crystal-related arthropathies - F. Salaffi; E. Filippucci; M. Gutierrez; W. Grassi (PAGEPress Publications, 2011)
0Over last few years, the ultrasonography (US) generated an increasing popularity among rheumatologists due to excellent potentiality and numerous applications in rheumatology. Most of the published papers focus mainly to demonstrate the utility of US in early and chronic arthritis, short-term therapy monitoring and guidance for invasive procedures. Less attention has been paid to the potential of this technique in the field of crystal-related arthropathies. By virtue of the high resolution of "new generation" equipments, minimal crystal deposits can be detected even sometime when the radiography was negative. The aim of this paper was to present the principal findings in patients with crystal-related arthropathies.